Single-layer aluminum alloy material for brazing and method for manufacturing aluminum structure

A single-layer aluminum alloy with controlled Si, Fe, Mn, Mg, and Bi compositions forms MgBi-based compounds to address flux residue and high-cost issues, enabling flux-free brazing with improved joint formation in high-moisture environments.

JP7610383B2Active Publication Date: 2025-01-08UACJ CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020165986
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-01-08
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Existing aluminum alloy materials for brazing face issues such as flux residue, clogging, and high manufacturing costs, particularly in environments with high moisture and oxygen, and they struggle to form a sound joint without using flux.

Method used

A single-layer aluminum alloy material with specific compositions of Si, Fe, Mn, Mg, and Bi, forming MgBi-based compounds dispersed in an Al matrix, which concentrate Mg and Bi in the melt to destroy oxide films and facilitate flux-free brazing even in inert gas atmospheres with high moisture and oxygen.

Benefits of technology

The alloy material effectively suppresses oxide film growth, ensures efficient brazing with improved wetting and spreading, and reduces manufacturing costs by forming a sound joint without flux, even in environments with high moisture and oxygen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610383000004
    Figure 0007610383000004
  • Figure 0007610383000005
    Figure 0007610383000005
  • Figure 0007610383000006
    Figure 0007610383000006
Patent Text Reader

Abstract

To provide a monolayer aluminum alloy material capable of brazing without using a flux even in an inert gas atmosphere containing relatively much moisture and oxygen and a manufacturing method of an aluminum structure using the monolayer aluminum alloy material.SOLUTION: A monolayer aluminum alloy material for brazing includes Si: 1.5 mass% or larger and 3.5 mass% or smaller, Fe: 0.05 mass% or larger and 2.00 mass% or smaller, Mn: 0.1 mass% or larger and 2.0 mass% or smaller, Mg: 0.005 mass% or larger and 0.500 mas% or smaller, Bi: 0.010 mass% or larger and 0.500 mass% or smaller, a remainder has a chemical composition consisting of Al and inevitable impurities and has a metallic structure in which a MgBi system compound is dispersed in an Al matrix. An area ratio of the MgBi system compound at any cross section is 0.05% or larger.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a single-layer aluminum alloy material for brazing and a method for manufacturing an aluminum structure using the single-layer aluminum alloy material. [Background technology]

[0002] For example, aluminum products such as heat exchangers and machine parts have many parts made of aluminum materials (including aluminum and aluminum alloys; the same applies below). These parts are often brazed with a brazing sheet having a core material and a brazing material provided on at least one surface of the core material. A commonly used method for brazing aluminum materials is the flux brazing method, in which flux is applied to the surfaces of the parts to be joined, that is, the parts to be joined by brazing, and then brazing is performed.

[0003] However, in the flux brazing method, after brazing is completed, flux and its residue adhere to the surface of the aluminum product. Depending on the application of the aluminum product, these fluxes and their residues may cause problems. For example, in a heat exchanger in which electronic components are mounted, there is a risk of problems such as deterioration of surface treatability due to flux residue during manufacture. In addition, for example, in a water-cooled heat exchanger, there is a risk of problems such as clogging of the refrigerant passage due to flux and the like. Furthermore, in order to remove the flux and its residues, pickling treatment is required, and in recent years, the cost burden of this treatment has become a problem.

[0004] In order to solve this problem, a so-called flux-free brazing method has been proposed, in which brazing is performed in an inert gas atmosphere without applying flux to the surface of the parts to be joined. The brazing sheet used in the flux-free brazing method contains an element that weakens or destroys the oxide film in at least one layer of its laminated structure. Mg (magnesium) is often used as this type of element.

[0005] A brazing sheet is produced by forming a clad material by cladding a core sheet and a brazing material sheet together, and then rolling the clad material, which results in a problem that the manufacturing cost of the brazing sheet is relatively high.

[0006] Furthermore, in the field of, for example, automotive heat exchangers, there is a demand for thinner brazing sheets for the purpose of weight reduction, improved heat exchange performance, etc. When attempting to reduce the thickness of the brazing sheet, the thickness of the brazing filler metal becomes extremely thin, and it becomes difficult to control the thickness of the brazing filler metal within the desired range in the manufacturing process of the brazing sheet.

[0007] In response to these problems, a single-layer aluminum alloy material has been proposed that is configured to generate a small amount of molten liquid by heating and be brazed to a mating material. As an example of this type of aluminum alloy material, for example, Patent Document 1 discloses a single-layer aluminum alloy material containing 0.2 mass% to 2.0 mass% Mg.

[0008] Patent Document 2 discloses a single-layer aluminum alloy material containing 1.0 mass% to 5.0 mass% Si, 0.01 mass% to 2.0 mass% Fe, and one or more selected from 2.0 mass% or less Mg, 1.5 mass% or less Cu, and 2.0 mass% or less Mn, with the balance being Al and unavoidable impurities. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Patent No. 5021097 [Patent Document 2] Patent No. 5337326 Summary of the Invention [Problem to be solved by the invention]

[0010] However, the aluminum alloy materials described in Patent Documents 1 and 2 contain Mg, which is relatively easily oxidized, and therefore an oxide film is easily formed on the surface. In particular, when the moisture concentration or oxygen concentration in the brazing atmosphere is relatively high, a strong oxide film is formed on the surface of the aluminum alloy material due to the reaction between the moisture or oxygen in the brazing atmosphere and Mg, resulting in deterioration of brazability.

[0011] The present invention has been made in view of the above background, and aims to provide a single-layer aluminum alloy material that can be brazed without using flux even in an inert gas atmosphere containing relatively large amounts of moisture and oxygen, and a method for manufacturing an aluminum structure using this single-layer aluminum alloy material. [Means for solving the problem]

[0012] One aspect of the present invention has a chemical composition containing Si (silicon): 1.5% by mass to 3.5% by mass, Fe (iron): 0.05% by mass to 2.00% by mass, Mn (manganese): 0.1% by mass to 2.0% by mass, Mg (magnesium): 0.005% by mass to 0.500% by mass, Bi (bismuth): 0.010% by mass to 0.500% by mass, with the balance being Al (aluminum) and unavoidable impurities, It has a metal structure in which MgBi-based compounds are dispersed in an Al matrix. The single-layer aluminum alloy material for brazing has an area ratio of the MgBi-based compound of 0.05% or more in any cross section. Effect of the Invention

[0013] The single-layer aluminum alloy material for brazing (hereinafter referred to as "aluminum material") contains both Mg and Bi. The aluminum material can form MgBi-based compounds in the aluminum material by adjusting at least the chemical components to fall within the specific ranges.

[0014] The aluminum material contains an amount of MgBi-based compound that provides an area ratio of 0.05% or more in any cross section. By forming the specific amount of MgBi compound in the aluminum material, the amount of Mg dissolved in the Al matrix can be reduced, and the growth of an oxide film on the surface of the aluminum material in the initial stage of brazing heating can be suppressed even in an inert gas atmosphere containing relatively large amounts of moisture and oxygen.

[0015] In addition, the MgBi-based compound in the aluminum material melts before the aluminum material starts to melt, forming a molten liquid containing Mg and Bi. The Mg and Bi in the molten liquid diffuse to the material surface, and thus the oxide film present on the surface of the aluminum material and the mating material can be destroyed to some extent before the aluminum material starts to melt.

[0016] When the brazing heat is further advanced, the aluminum material melts and a molten liquid is formed. As described above, the oxide film existing on the surface of the aluminum material and the counter material is destroyed to some extent by Mg and Bi generated from the MgBi-based compound before the molten liquid of the aluminum material is formed. Therefore, the molten liquid generated from the aluminum material can easily wet and spread on the surface of the counter material.

[0017] In addition, by setting the chemical composition of the aluminum material to the specific range, Mg and Bi can be concentrated in the melt. Therefore, when the melt of the aluminum material contacts the surface of the mating material, the destruction of the oxide film remaining on the surface of the mating material can be further promoted. As a result, the aluminum material can easily form a sound brazing joint without using a flux.

[0018] Therefore, the single-layer aluminum alloy material for brazing can be brazed to a mating material without using flux even in an inert gas atmosphere containing a comparatively large amount of moisture and oxygen. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is an explanatory diagram illustrating the principle by which Mg is concentrated from an aluminum material into a melt. [Diagram 2] FIG. 2 is an explanatory diagram of an example in which Mg concentration in the melt hardly occurs. [Diagram 3] FIG. 3 is a perspective view of a mini-core test piece in Example 2. [Figure 4] FIG. 4 is a partially enlarged cross-sectional view of a brazed joint between a plate and a corrugated fin in Example 2. As shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] (Single layer aluminum alloy material for brazing) The single-layer aluminum alloy material for brazing is composed of a single layer of an aluminum alloy having the above-mentioned chemical components. The chemical components of the aluminum material and the reasons for their limitations will be explained below.

[0021] Si (silicon): 1.5% by mass or more and 3.5% by mass or less The aluminum material contains 1.5% by mass or more and 3.5% by mass or less of Si as an essential component. By making the content of Si in the aluminum material 1.5% by mass or more, a small amount of molten liquid containing Al, Si, Mg and Bi can be generated by brazing heat, and brazing with a mating material can be performed. The content of Si is preferably 2.0% by mass or more. In this case, the amount of molten liquid generated by brazing heat can be increased, and brazing properties can be further improved. If the content of Si is less than 1.5% by mass, the amount of molten liquid generated by brazing heat is insufficient, which may lead to deterioration of brazing properties.

[0022] On the other hand, if the Si content is excessively high, the amount of melting of the aluminum material increases during brazing heating, which may lead to a decrease in the strength of the aluminum material. As a result, the shape of the assembly including the aluminum material may not be maintained during brazing. In order to avoid such problems, the Si content is set to 3.5 mass% or less. From the same viewpoint, it is preferable that the Si content is set to 3.0 mass% or less.

[0023] In addition, by setting the Si content within the above-mentioned specific range, Mg can be concentrated in the molten liquid generated from the aluminum material by the brazing heat. As a result, the oxide film of the mating material can be efficiently destroyed with a relatively small amount of Mg, and brazing to the mating material can be performed. The reason for this will be explained with reference to Figs. 1 and 2.

[0024] 1 and 2 are both isothermal cross-sectional views at a temperature of 590° C. of an Al-Si-Mg ternary phase diagram calculated using the thermodynamic calculation system “Thremo-Calc (registered trademark).” The axis extending from the lower left vertex to the lower right vertex of the diagram represents the Mg content (unit: mass%), and the axis extending from the lower left vertex to the upper vertex represents the Si content (unit: mass%).

[0025] The region indicated by the symbol L is the liquid phase state, the region indicated by the symbol S is the solid phase state, and the region indicated by the symbol L+S is the coexistence state of solid and liquid phases, with the boundary between the solid phase and the coexistence state being the solidus line a, and the boundary between the coexistence state and the liquid phase being the liquidus line b. Within the region showing the coexistence state of solid and liquid phases, tie lines for various compositions are indicated by dashed lines.

[0026] When an aluminum material having a composition indicated by point P1 on tie line t1 in Fig. 1 is heated to 590°C, the aluminum material melts very slightly and a small amount of molten liquid is formed. The composition of the molten liquid at this time is the composition indicated by the intersection point Q1 between the tie line t1 on which point P1 is located and the liquidus line b.

[0027] Comparing the Mg content at point P1 and the Mg content at point Q1 based on Fig. 1, the Mg content at point Q1 is higher than the Mg content at point P1. It can therefore be understood that when an aluminum material having the composition shown by point P1 is heated, the Mg content in the melt becomes higher than the Mg content in the aluminum material before heating, and Mg is concentrated in the melt.

[0028] On the other hand, Fig. 2 shows point P2, which is obtained by increasing only the Si content from the composition represented by point P1 so as to obtain a composition on tie line t2. When an aluminum material having the composition represented by point P2 is heated to 590°C, the aluminum material melts and a molten liquid is formed. The composition of the molten liquid at this time becomes the composition represented by the intersection point Q2 between the tie line t2 on which point P2 is located and the liquidus line b.

[0029] 2, comparing the Mg content at point P2 and the Mg content at point Q2, it can be seen that the Mg content at point Q2 is approximately the same as the Mg content at point P2. Therefore, it can be seen that when an aluminum material having the composition shown by point P2 is heated, the Mg content in the melt becomes approximately the same as that of the aluminum material before heating, and there is almost no concentration of Mg in the melt.

[0030] The aluminum material actually contains not only Al, Si, and Mg, but also other elements such as Fe and Bi. Therefore, the Mg content in the melt may be slightly different from the value based on the Al-Si-Mg ternary phase diagram described above. However, the inventors have conducted extensive research and found that by setting the amount of Si in the aluminum material to the specific range, Mg can be effectively concentrated in the melt of the aluminum material, leading to the completion of the present invention.

[0031] Mg (Magnesium): 0.005% by mass or more and 0.500% by mass or less The aluminum material contains 0.005% by mass or more and 0.500% by mass or less of Mg as an essential component. The Mg atoms in the aluminum material are present in the form of solid-solved Mg in an Al matrix, MgBi-based compounds, etc. Mg has the effect of destroying an oxide film present in the aluminum material or on the surface of a mating material to be joined to the aluminum material. By setting the Mg content in the aluminum material to the specific range, a sound brazing joint can be formed with the mating material even in an inert gas atmosphere containing a relatively large amount of moisture and oxygen.

[0032] If the Mg content in the aluminum material is less than 0.005% by mass, the Mg content in the molten aluminum material is insufficient, which may lead to deterioration of brazing properties. Therefore, from the viewpoint of avoiding deterioration of brazing properties due to insufficient Mg, the Mg content in the aluminum material is set to 0.005% by mass or more. From the viewpoint of increasing the Mg content in the molten aluminum material, the Mg content in the aluminum material is preferably set to 0.010% by mass or more, and more preferably set to 0.020% by mass or more.

[0033] On the other hand, if the Mg content is excessively high, a strong oxide film may be formed on the surface of the aluminum alloy material due to the reaction between Mg and moisture or oxygen contained in a small amount in the brazing atmosphere, which may lead to deterioration of brazing properties. In this case, the strength of the aluminum material may decrease during brazing, and deformation or buckling of the aluminum material may occur. In order to avoid these problems, the Mg content in the aluminum material is set to 0.500 mass% or less. From the same viewpoint, the Mg content in the aluminum material is preferably 0.200 mass% or less, and more preferably 0.050 mass% or less.

[0034] In addition, it is preferable that the aluminum material is configured so that, when the aluminum material is heated at 590°C, a molten liquid can be formed in which the Mg content is 0.010 mass% or more and is 1.5 times or more the Mg content in the aluminum material before heating.

[0035] According to this aluminum material, even when the aluminum material has a relatively low Mg content, the amount of Mg in the melt can be sufficiently increased, and as a result, the oxide film present on the surface of the mating material during brazing can be destroyed, thereby further improving brazeability.

[0036] From the viewpoint of further improving brazing properties, the aluminum material is preferably configured so as to form a molten liquid having a Mg content of 0.030% by mass or more when heated at 590°C, and more preferably configured so as to form a molten liquid having a Mg content of 0.100% by mass or more.

[0037] Bi (Bismuth): 0.010% by mass or more and 0.500% by mass or less The aluminum material contains 0.010% by mass or more and 0.500% by mass or less of Bi as an essential component. Bi in the aluminum material forms an MgBi-based compound together with Mg. Bi improves the fluidity of the melt generated by brazing heat and weakens the oxide film present in the aluminum material and on the surface of the mating material to be joined to the aluminum material.

[0038] By making the content of Bi in the aluminum material 0.010% by mass or more, Bi is easily concentrated in the oxide film. Then, by concentrating Bi in the oxide film, the effect of weakening the oxide film by Bi and the effect of destroying the oxide film by Mg act synergistically, and the oxide film can be effectively destroyed. In addition, by making the content of Bi in the aluminum material 0.010% by mass or more, the fluidity of the melt can be improved. As a result, brazing properties can be improved even in an inert gas atmosphere containing a relatively large amount of moisture and oxygen. If the content of Bi in the aluminum material is less than 0.010% by mass, the above-mentioned action and effect of Bi becomes insufficient, which may lead to deterioration of brazing properties.

[0039] On the other hand, if the Bi content is excessively high, simple Bi is likely to precipitate during the manufacturing process of the aluminum material, which may lead to a decrease in the manufacturability of the aluminum material. From the viewpoint of avoiding such a problem, the Bi content is set to 0.500 mass% or less. From the same viewpoint, the Bi content is preferably 0.200 mass% or less, and more preferably 0.100 mass% or less.

[0040] Area ratio of MgBi-based compounds: 0.05% or more The aluminum material has a metal structure in which MgBi-based compounds containing Mg and Bi are dispersed in an Al matrix, and the area ratio of the MgBi-based compounds in any cross section of the aluminum material is 0.05% or more.

[0041] When MgBi-based compounds are formed as second phase particles in the Al matrix, the amount of dissolved Mg in the Al matrix becomes relatively small, making the Al matrix less susceptible to oxidation. By forming MgBi-based compounds in an aluminum material in an amount such that the area ratio in any cross section is 0.05% or more, the growth of an oxide film on the surface of the aluminum material in the early stage of brazing can be suppressed.

[0042] In addition, as the brazing progresses and the temperature of the aluminum material rises, the MgBi-based compound melts and forms a molten liquid containing Mg and Bi. This molten liquid acts as a supply source of Mg and Bi to the material surface. Therefore, by forming the MgBi-based compound in the aluminum material, the oxide film present on the surface of the aluminum material and the mating material can be destroyed to some extent before the aluminum material melts. In addition, after the aluminum material melts, Mg and Bi are supplied from the molten MgBi-based compound to the molten liquid of the aluminum material, so that the Mg concentration and Bi concentration in the molten liquid can be sufficiently increased. As a result, the oxide film present on the surface of the aluminum material and the mating material can be effectively destroyed.

[0043] Therefore, by making the area ratio of the MgBi-based compound in any cross section of the aluminum material 0.05% or more, brazing can be performed while suppressing oxidation of the aluminum material and the mating material even in an inert gas atmosphere containing a relatively large amount of moisture and oxygen. From the viewpoint of more reliably achieving the above-mentioned effects, the area ratio of the MgBi-based compound in any cross section of the aluminum material is preferably 0.07% or more, and more preferably 0.10% or more.

[0044] From the viewpoint of further enhancing the above-mentioned action and effect, there is no upper limit to the area ratio of the MgBi-based compounds in any cross section of the aluminum material, but in an aluminum material having the specific chemical composition, the area ratio of the MgBi-based compounds is usually 20% or less. The area ratio of the MgBi-based compounds is preferably 10% or less, more preferably 7% or less, and even more preferably 5% or less.

[0045] Fe (iron): 0.05% by mass or more and 2.00% by mass or less The aluminum material contains 0.05% by mass or more and 2.00% by mass or less of Fe as an essential component. Fe is dispersed as a crystallized product in the aluminum material, and has the effect of suppressing a decrease in strength, particularly at high temperatures. By setting the Fe content to 0.05% by mass or more, such an effect can be sufficiently obtained. From the viewpoint of more effectively suppressing a decrease in strength at high temperatures, it is preferable that the Fe content be 0.10% by mass or more.

[0046] If the Fe content is less than 0.05% by mass, the strength of the aluminum material at high temperatures may decrease, and in this case, it is necessary to use high-purity metal in the production of the aluminum material, which increases the cost.

[0047] On the other hand, if the Fe content exceeds 2.00 mass%, coarse intermetallic compounds are likely to be generated during casting in the manufacturing process of the aluminum material. In this case, the crystal grains of the Al matrix are likely to be refined by recrystallization during brazing. As a result, the grain boundary density of the Al matrix increases, and buckling may occur more easily.

[0048] Mn (manganese): 0.1% by mass or more and 2.0% by mass or less The aluminum material contains 0.1% by mass or more and 2.0% by mass or less of Mn as an essential component. Mn forms an Al-Mn-Si intermetallic compound in the aluminum material, and has the effect of improving the strength of the aluminum material by dispersion strengthening. Mn also dissolves in the Al matrix, and has the effect of improving the strength of the aluminum material by solid solution strengthening.

[0049] By making the Mn content in the aluminum material 0.1% by mass or more, the strength of the aluminum material can be improved by dispersion strengthening and solid solution strengthening. Furthermore, the aluminum material can suppress a decrease in strength during brazing heating and suppress the occurrence of deformation and buckling of the aluminum material due to the above-mentioned dispersion strengthening and solid solution strengthening. If the Mn content is less than 0.1% by mass, the effect of improving strength by Mn is reduced, and the aluminum material may be more likely to deform or buckle.

[0050] On the other hand, if the Mn content is excessively high, coarse intermetallic compounds are likely to be formed during the manufacturing process of the aluminum material. If rolling is performed while the coarse intermetallic compounds are included, there is a risk that pinholes are likely to be generated. In order to avoid such problems, the Mn content is set to 2.0 mass% or less.

[0051] The chemical components of the aluminum material may be composed of only the above-mentioned essential components, Al, and unavoidable impurities. In other words, the aluminum material may contain only Si: 1.5 mass% to 3.5 mass%, Fe: 0.015 mass% to 2.00 mass%, Mn: 0.1 mass% to 2.0 mass%, Mg: 0.005 mass% to 0.500 mass%, Bi: 0.010 mass% to 0.500 mass%, Al, and unavoidable impurities. In addition to the above-mentioned essential components, the chemical components of the aluminum material may further contain optional elements such as Zn (zinc), In (indium), Sn (tin), Cu (copper), Zr (zirconium), Ti (titanium), Sr (strontium), Na (sodium), and Sb (antimony).

[0052] ·Zn: 6.0% by mass or less The aluminum material may contain 0% by mass or more and 6.0% by mass or less of Zn as an optional component. Zn has the effect of improving the corrosion resistance of the aluminum structure after brazing. When the aluminum material is heated to the brazing temperature, Zn in the aluminum material is dissolved into the molten liquid, and Zn is concentrated in the molten liquid. When the molten liquid is solidified after brazing, the potential of the surface of the aluminum material and the brazing joint formed between the aluminum material and the counter material is reduced, and these parts can function as sacrificial corrosion inhibitors.

[0053] By making the Zn content in the aluminum material greater than 0% by mass, the above-mentioned effect can be exerted, and the corrosion resistance of the aluminum structure can be further improved. From the viewpoint of further improving the corrosion resistance, the Zn content in the aluminum material is preferably 0.05% by mass or more, and more preferably 0.5% by mass or more.

[0054] On the other hand, if the Zn content is excessively high, the self-corrosion resistance of the aluminum material may be reduced. By setting the Zn content to 6.0 mass% or less, preferably 4.0 mass% or less, and more preferably 3.0 mass% or less, such a problem can be more reliably avoided.

[0055] In: 0.1% by mass or less The aluminum material may contain 0% by mass or more and 0.1% by mass or less of In as an optional component. In, like Zn, has the effect of improving the corrosion resistance of the aluminum structure after brazing. When the aluminum material is heated to the brazing temperature, In in the aluminum material is dissolved into the molten liquid, and In is concentrated in the molten liquid. When this molten liquid is solidified after brazing, the potential of the surface of the aluminum material and the brazing joint formed between the aluminum material and the counterpart material is reduced, and these parts can function as sacrificial corrosion inhibitors.

[0056] By making the In content in the aluminum material greater than 0 mass%, the above-mentioned effect can be exerted, and the corrosion resistance of the aluminum structure can be further improved. From the viewpoint of further improving the corrosion resistance, the In content in the aluminum material is preferably 0.005 mass% or more, and more preferably 0.01 mass% or more.

[0057] On the other hand, if the In content is excessively high, the self-corrosion resistance of the aluminum material may be reduced. By setting the In content to 0.1 mass% or less, preferably 0.05 mass% or less, such a problem can be more reliably avoided.

[0058] Sn: 0.1% by mass or less The aluminum material may contain 0% by mass or more and 0.1% by mass or less of Sn as an optional component. Sn has the effect of improving the corrosion resistance of the aluminum structure after brazing, similar to Zn. When the aluminum material is heated to the brazing temperature, Sn in the aluminum material is dissolved into the molten liquid, and Sn is concentrated in the molten liquid. When this molten liquid is solidified after brazing, the potential of the surface of the aluminum material and the brazing joint formed between the aluminum material and the counter material is reduced, and these parts can function as sacrificial corrosion inhibitors.

[0059] By making the Sn content in the aluminum material greater than 0% by mass, the above-mentioned effect can be exerted, and the corrosion resistance of the aluminum structure can be further improved. From the viewpoint of further improving the corrosion resistance, the Sn content in the aluminum material is preferably 0.005% by mass or more, and more preferably 0.01% by mass or more.

[0060] On the other hand, if the Sn content is excessively high, the self-corrosion resistance of the aluminum material may be reduced. By setting the Sn content to 0.1 mass% or less, preferably 0.05 mass% or less, such a problem can be avoided more reliably.

[0061] Cu: 0.6% by mass or less The aluminum material may contain 0% by mass or more and 0.6% by mass or less of Cu as an optional component. Cu has the effect of being dissolved in an Al matrix to improve the strength of the aluminum material. By making the Cu content in the aluminum material greater than 0% by mass, this effect can be exerted and the strength of the aluminum material can be further improved. From the viewpoint of further improving the strength of the aluminum material, the Cu content in the aluminum material is preferably 0.05% by mass or more.

[0062] On the other hand, if the Cu content is excessively high, the amount of melting of the aluminum material increases during brazing heating, resulting in a decrease in the strength of the aluminum material. As a result, there is a risk that the shape of the assembly cannot be maintained during brazing. In addition, if the Cu content is excessively high, there is a risk that the corrosion resistance of the aluminum material decreases. By setting the Cu content to 0.6 mass% or less, preferably 0.4 mass% or less, and more preferably 0.2 mass% or less, these problems can be more reliably avoided.

[0063] Zr: 0.3% by mass or less The aluminum material may contain 0% by mass or more and 0.3% by mass or less of Zr as an optional component. Zr has the effect of increasing the strength before and after brazing, coarsening the crystal grain size after brazing, and increasing the high-temperature buckling resistance and brazeability. By increasing the Zr content in the aluminum alloy to more than 0% by mass, it is possible to exert such an effect, further improving the strength before and after brazing, and further improving the high-temperature buckling resistance and brazeability.

[0064] On the other hand, if the Zr content in the aluminum alloy is excessively high, coarse crystals are likely to be generated during the manufacturing process of the aluminum material. By setting the Zr content in the aluminum material to 0.3 mass% or less, such a problem can be more reliably avoided.

[0065] Ti: 0.3% by mass or less The aluminum material may contain 0% by mass or more and 0.3% by mass or less of Ti as an optional component. Ti dissolves in the Al matrix to improve strength, and distributes in layers in the aluminum material to prevent corrosion from progressing in the plate thickness direction. By increasing the Ti content in the aluminum material to more than 0% by mass, these effects can be achieved.

[0066] On the other hand, if the Ti content is excessively high, coarse intermetallic compounds are likely to be formed during the manufacturing process of the aluminum material. If the aluminum material is rolled while containing these coarse intermetallic compounds, the coarse intermetallic compounds may cause the aluminum material to easily crack. By setting the Ti content in the aluminum material to 0.3 mass% or less, preferably 0.2 mass% or less, such problems can be avoided more reliably.

[0067] ·Sr: 0.1% by mass or less, Na: 0.1% by mass or less, Sb: 0.3% by mass or less The aluminum material may contain, as an optional component, one or more elements selected from the group consisting of 0% by mass to 0.1% by mass of Sr, 0% by mass to 0.1% by mass of Na, and 0% by mass to 0.3% by mass of Sb. These elements have the effect of refining Si particles in the aluminum material and uniformly dispersing the Si particles on the surface of the aluminum material. Since the Si particles are the starting points for the formation of a molten liquid, by uniformly dispersing the Si particles on the surface of the aluminum material, a molten liquid can be formed uniformly on the surface of the aluminum material.

[0068] By making the content of the above-mentioned elements in the aluminum material larger than 0% by mass, a uniform melt can be formed on the surface of the aluminum material, and a larger amount of melt can be supplied to the portion to be joined with the mating material. As a result, brazing properties can be improved. On the other hand, if the content of the above-mentioned elements is excessively large, compounds of these elements with Mg or Bi are likely to be formed during casting, which may make casting difficult. By setting the Sr content, Na content, and Sb content within the specific ranges, respectively, such problems can be easily avoided. From the same viewpoint, the Sr content is preferably 0.05% by mass or less, the Na content is preferably 0.05% by mass or less, and the Sb content is preferably 0.2% by mass or less.

[0069] The aluminum material may contain elements such as Ag, B, Be, Ca, Cd, Co, Ga, Ge, Hg, Li, Mo, Ni, P, Pb, V, and Y as inevitable impurities. The content of these elements as inevitable impurities is usually 0.05 mass% or less for each element. The total amount of inevitable impurities contained in the aluminum material is preferably 0.15 mass% or less.

[0070] The shape of the aluminum material is not particularly limited. For example, the aluminum material may be a plate material or a bar material. When the aluminum material is a plate material, the aluminum material preferably has a plate thickness of less than 0.15 mm. As described above, the conventional brazing sheet has a problem that when the thickness of the entire brazing sheet is reduced, the thickness of the brazing material may become extremely thin, and it is difficult to control the thickness of the brazing material within a desired range.

[0071] The aluminum material melts very slightly when heated for brazing, and the molten liquid can seep out from the entire surface. Therefore, even if the plate thickness is thin, a sufficient amount of molten liquid can be generated. In addition, since the aluminum material is composed of a single layer, the manufacturing cost can be reduced compared to conventional brazing sheets. Therefore, the thinner the plate thickness, the greater the effect of improving brazing properties and reducing manufacturing costs by the aluminum material. In particular, for very thin plate thicknesses of less than 0.15 mm, the aluminum material is more advantageous than conventional brazing sheets in terms of both brazing properties and cost.

[0072] (Method of manufacturing aluminum structure) Brazing using the aluminum material can be carried out, for example, as follows: First, an assembly including the aluminum alloy material is prepared. The assembly may be composed of only the aluminum material, or may include the aluminum material and other aluminum parts.

[0073] For example, when manufacturing a heat exchanger as an aluminum structure, a heat exchanger core can be manufactured as an assembly by alternately stacking corrugated fins made of the aluminum material and separately prepared flat multi-hole tubes. Furthermore, a header or the like may be attached to this heat exchanger core.

[0074] This assembly is heated without applying flux under heating conditions where the temperature is within the range of 580 to 590°C for 30 seconds or more. The atmosphere during brazing is preferably an inert gas atmosphere. Examples of inert gas that can be used include nitrogen and argon. The dew point of the inert gas is 、- The temperature is more preferably 50° C. or lower, and particularly preferably −60° C. or lower. The oxygen concentration in the inert gas atmosphere is 、1 It is more preferable that the concentration is 00 ppm by volume or less, further preferably 10 ppm by volume or less, and particularly preferably 5 ppm by volume or less.

[0075] The aluminum material has the specific chemical components and a metal structure in which MgBi-based compounds are dispersed in an Al matrix. Therefore, the aluminum material can exhibit good brazing properties even in an inert gas atmosphere with a dew point of -50°C or less and an oxygen concentration of 100 ppm by volume or less, which contains relatively large amounts of moisture and oxygen for a flux-free brazing method.

[0076] The aluminum material is melted by heating the assembly in the inert gas atmosphere, and a molten liquid is formed. The aluminum material and a mating material are brazed with the molten liquid to obtain an aluminum structure.

[0077] In the method for producing an aluminum structure using the aluminum alloy material, it is preferable that at least one of the aluminum material and a mating material that comes into contact with the aluminum alloy material in the assembly is etched.

[0078] That is, when producing an aluminum structure using the aluminum material, An assembly is produced, which includes the brazing single-layer aluminum alloy material and a mating material in contact with the brazing single-layer aluminum alloy material, and at least one of the brazing single-layer aluminum alloy material and the mating material is etched; The assembly is heated under heating conditions such that the temperature is within a range of 580 to 590°C for 30 seconds or more, thereby melting a portion of the single-layer aluminum alloy material to form a molten liquid; It is preferable that the aluminum structure is produced by brazing the assembly with the melt.

[0079] In this way, by performing brazing in a state where at least one of the aluminum material and the mating material is etched, brazing can be performed in a state where the oxide film present in the portion where the brazing joint is to be formed is more fragile, which makes it possible to further improve brazing properties even in an inert gas atmosphere containing relatively large amounts of moisture and oxygen.

[0080] The timing of etching the aluminum material and / or the mating material is not particularly limited as long as it is performed before the brazing heat is performed. For example, an assembly may be produced using an aluminum material or a mating material that has been previously etched, or the assembly may be produced and then etched together.

[0081] The etching method is not particularly limited, and for example, a method of contacting the aluminum material and / or the counter material with an acid or alkali can be adopted. In the etching, the oxide film present on the surface of the aluminum material or the counter material may be completely removed before etching, or a part of the oxide film may be removed. After the etching is completed, post-treatment such as washing with water or removing smut generated by etching may be performed as necessary. EXAMPLES

[0082] The examples of the brazing single-layer aluminum alloy material are described below. Note that the specific aspects of the brazing single-layer aluminum alloy material and the manufacturing method thereof according to the present invention are not limited to the following examples, and the configurations can be appropriately changed within the scope of the present invention.

[0083] Example 1 In this example, an example of the single-layer aluminum alloy material for brazing and its manufacturing method will be described. The aluminum material of this example contains Si: 1.5 mass% to 3.5 mass%, Fe: 0.05 mass% to 2.00 mass%, Mn: 0.1 mass% to 2.0 mass%, Mg: 0.005 mass% to 0.500 mass%, Bi: 0.010 mass% to 0.500 mass%, and contains one or two elements of Cu: 0 mass% to 0.6 mass% and Sr: 0 mass% to 0.1 mass% as optional components, with the balance being Al and unavoidable impurities. In addition, the aluminum material of this example has a metal structure in which MgBi-based compounds are dispersed in an Al matrix, and the area ratio of the MgBi-based compounds in any cross section is 0.05% or more. Hereinafter, a more specific configuration of the aluminum material will be described together with a manufacturing method.

[0084] [Aluminum material manufacturing method] The aluminum material of this example can be produced, for example, by rolling a cast plate produced by a twin-roll continuous casting and rolling method. Specifically, first, a cast plate having the chemical components shown in Table 1 is produced by a twin-roll continuous casting and rolling method. The temperature of the molten metal during casting may be appropriately set within a range of, for example, 650 to 800°C. The casting speed may be appropriately set within a range of, for example, 0.5 to 2.0 mm / min. The dimensions of the cast plate are not particularly limited, but may be, for example, 6 mm thick. In Table 1, the symbol "-" indicates that the content of the element is below the detection limit of an optical emission spectrometer (a so-called quantum meter), and the symbol "Bal." indicates the remainder.

[0085] Thereafter, an aluminum material can be obtained by appropriately combining rolling and heat treatment according to the desired thickness and quality. For example, to obtain an aluminum material having a thickness of 0.20 mm and tempered to O material, the cast plate is held at a temperature of 360°C for 3 hours for intermediate annealing. The cast plate after intermediate annealing is cold rolled to obtain a rolled plate having a thickness of 0.20 mm, and then the rolled plate is annealed by holding it at a temperature of 360°C for 3 hours.

[0086] In addition, when it is desired to obtain an aluminum material having a thickness of 0.070 mm and tempered to H14 material, the cast plate is cold-rolled to a rolled plate having a thickness of 0.100 mm. The rolled plate is then held at a temperature of 360° C. for 3 hours for intermediate annealing. The rolled plate after intermediate annealing is then further cold-rolled to a thickness of 0.070 mm.

[0087] By the above, it is possible to obtain aluminum materials (Table 1, test materials S1 to S8 and test materials S15 to S17) having the specific chemical composition and metal structure. The test materials S9 to S14 and S18 to S25 shown in Table 1 are test materials for comparison with the test materials S1 to S8 and the test materials S15 to S17. The chemical composition, quality and thickness of each test material are as shown in Table 1. For the test materials S11, S14, S21, S23 and S25 shown in Table 1, the content of Bi, Fe, Mn or Sr in the chemical composition is higher than the specific range, so it is difficult to produce a cast plate by the twin-roll continuous casting and rolling method. Therefore, the following evaluation of these test materials is omitted.

[0088] In the above-mentioned manufacturing method, an example of a method for producing an aluminum material from a cast plate obtained by a twin-roll continuous casting and rolling method has been described, but the method for producing a cast plate is not limited to the twin-roll continuous casting and rolling method, and other methods such as DC casting can also be used. When producing an aluminum material from a cast plate obtained by a DC casting method, for example, the following conditions may be used.

[0089] That is, first, an ingot having the chemical composition shown in Table 1 is produced by DC casting, and then the ingot is held at a temperature of 520 ° C for 3 hours to perform homogenization treatment. Then, hot rolling is performed while holding the temperature at 520 ° C to obtain a rolled plate having a thickness of 3 mm. This rolled plate is subjected to a suitable combination of rolling and heat treatment according to the desired thickness and quality, thereby obtaining an aluminum material. For example, when an aluminum material having a thickness of 0.070 mm and tempered to H14 material is to be obtained, the rolled plate is subjected to cold rolling to a thickness of 0.097 mm. Next, the rolled plate is held at a temperature of 360 ° C for 3 hours to perform intermediate annealing. Then, the rolled plate after intermediate annealing is further subjected to cold rolling to a thickness of 0.070 mm.

[0090] [Measurement of area ratio of MgBi-based compounds] The method for measuring the area ratio of MgBi-based compounds in an aluminum material is as follows. First, the aluminum material is cut to prepare a sample with an exposed L-ST surface (i.e., a surface parallel to both the rolling direction and thickness direction of the aluminum material). The L-ST surface of the sample is mirror-polished, and then gold is vapor-deposited on the L-ST surface. Then, a surface analysis is performed using an EPMA (i.e., an electron probe microanalyzer) to obtain an elemental map of Bi on the L-ST surface. The area ratio of Bi to the field of view is calculated by performing image analysis on the elemental map of Bi.

[0091] It is estimated that Bi exists only as MgBi-based compounds within the range of chemical composition of the aluminum material according to the present invention. Therefore, in this example, the area ratio of Bi calculated based on the element map of Bi can be regarded as the area ratio of MgBi-based compounds. The area ratio of MgBi-based compounds of each test material is the value shown in Table 1.

[0092] [Table 1]

[0093] Example 2 In this example, a mini-core test specimen simulating a core of a heat exchanger is produced using the aluminum material obtained in Example 1, and brazeability and buckling resistance are evaluated based on the brazing results of the mini-core test specimen.

[0094] [Preparation of mini-core specimen] As shown in Fig. 3, the mini-core specimen 1 of this example has two plates 2 and a corrugated fin 3 interposed between the plates 2, and the plates 2 and the corrugated fin 3 are joined to each other by brazing. The thickness of the plate 2 is 0.20 mm. The thickness of the corrugated fin 3 is 0.070 mm, the width is 16 mm, the crest height is 10 mm, and the pitch is 3 mm. The number of portions where the plate 2 and the corrugated fin 3 are in contact with each other is 20 in total.

[0095] Specifically, any one of the test materials S1 to S6, S9 to S10, S12 to S13 in Example 1 or a plate material having a thickness of 0.20 mm made of A3003 alloy is used as the plate 2. Also, any one of the test materials S7 to S8 in Example 1 or a plate material having a thickness of 0.070 mm made of A3003 alloy is used as the corrugated fin 3.

[0096] In preparing the mini-core specimen 1, first, either the plate 2 or the corrugated fin 3 is etched as shown in Table 2. Specifically, the plate 2 or the corrugated fin 3 is immersed in an etching solution for 90 seconds to remove the oxide film present on the surface. Thereafter, the etched plate 2 or the corrugated fin 3 is washed with water and then dried. As the etching solution, for example, a mixture of a 2% aqueous solution of hydrofluoric acid and a 1% aqueous solution of nitric acid can be used.

[0097] The plates 2 and corrugated fins 3 thus prepared are stacked in the combinations shown in Table 2 to prepare an assembly. When preparing the assembly, no flux is applied to the plates 2 and the corrugated fins 3. The assembly is restrained using a stainless steel jig, and then placed in a brazing furnace for brazing. In this example, brazing is performed in a nitrogen atmosphere with an oxygen concentration of 80 ppm by volume and a dew point of -50°C. During brazing, the assembly is heated so that the time required for the temperature in the brazing furnace to reach 590°C from the time it reaches 580°C is 70 seconds.

[0098] When the assembly is heated and the temperature exceeds the solidus of the test material (i.e., the single-layer aluminum alloy material for brazing), the entire test material melts slightly and a molten liquid containing Al, Si, Mg, and Bi is formed. When the molten liquid seeping out of the test material comes into contact with the oxide film on the surface of the test material or the mating material, the Al2O3 that constitutes the oxide film is reduced by Mg to become a spinel-type oxide (Al2MgO4). This destroys the oxide film on the surface of the test material or the mating material, and a brazing joint is formed between the test material and the mating material.

[0099] That is, for example, when the corrugated fin 3 is made of the test material, the oxide film present on the surfaces of the corrugated fin 3 and the plate 2 is destroyed by the molten liquid seeping out from the corrugated fin 3. Then, as shown in Fig. 4, a fillet 4 is formed between the corrugated fin 3 and the plate 2 as the molten liquid solidifies, and the corrugated fin 3 and the plate 2 are brazed together.

[0100] By the above steps, it is possible to obtain the mini-core specimens 1 shown in the experiment numbers A1 to A8 in Table 2. The mini-core specimens 1 shown in the experiment numbers A9 to A12 in Table 2 are mini-core specimens 1 for comparison with the mini-core specimens 1 shown in the experiment numbers A1 to A8.

[0101] [Evaluation of brazing] The brazing property of the single-layer aluminum alloy material for brazing can be evaluated based on the bonding rate between the plate 2 and the corrugated fin 3 in the mini-core test piece 1. The bonding rate is calculated specifically as follows. First, the corrugated fin 3 is peeled off from the mini-core test piece 1 after brazing to expose the traces of the fillets 4 formed on the plate 2. Then, the number of traces of the fillets 4 formed over the entire width direction of the plate 2 is counted. The bonding rate is determined as the ratio of the number of traces of the fillets 4 formed over the entire width direction of the tube to the total number of contact points between the plate 2 and the corrugated fin 3 (i.e., 20 points).

[0102] The brazeability of each test material is shown in the "Brazeability" column of Table 2. The meanings of the symbols A to C in this column are as follows. In the evaluation of brazeability, symbols A and B, which have a joining rate of 40% or more, are judged to be pass because of excellent brazeability, and symbols C, which have a joining rate of less than 40%, are judged to be fail because of poor brazeability. A: The bonding rate is 60% or more. B: The bonding rate is 40% or more but less than 60%. C: The bonding rate is less than 40%.

[0103] [Evaluation of buckling resistance] The buckling resistance of the single-layer aluminum alloy material for brazing can be evaluated based on the reduction rate of the height of the corrugated fin 3 due to brazing, that is, the ratio of the amount of reduction in the height of the corrugated fin 3 due to brazing to the height of the corrugated fin 3 before brazing. If the strength of the corrugated fin 3 made of the single-layer aluminum alloy material for brazing decreases during brazing and buckling or deformation occurs, the height of the corrugated fin 3 after brazing will be lower than the height of the corrugated fin 3 before brazing.

[0104] In this example, the reduction rate of the height of the corrugated fin 3 was calculated for the mini-core specimen 1 (i.e., experiment numbers A7 to A8 in Table 2) having the corrugated fin 3 made of a single-layer aluminum alloy material for brazing. In the "Buckling resistance" column in Table 2, "Good" was entered when the reduction rate of the height was 10% or less, and "Poor" was entered when it exceeded 10%. Note that for the mini-core specimen 1 having the corrugated fin 3 made of the A3003 alloy, the reduction rate of the height of the corrugated fin 3 was not calculated, and therefore the symbol "-" was entered in the "Buckling resistance" column in Table 2.

[0105] [Table 2]

[0106] Test materials S1 to S8 (see Table 1) having the specific chemical components were used for the mini-core test specimens 1 shown in Experiment Nos. A1 to A8 in Table 2. These test materials S1 to S8 exhibit excellent brazing properties even in an inert gas atmosphere with a relatively high moisture and oxygen content for a flux-free brazing method, and can increase the joining rate of the mini-core test specimens 1. Among these test materials, test materials S1 to S5 and test material S8 in particular exhibit superior brazing properties compared to test materials S6 and S7, which have a higher Mg content than these test materials.

[0107] In addition, the single-layer aluminum alloy material for brazing having the specific chemical composition has excellent buckling resistance, so that the use of the corrugated fin 3 made of such an aluminum material can suppress a reduction in the height of the corrugated fin 3 due to brazing.

[0108] On the other hand, for the mini-core specimen 1 shown in experiment number A9 in Table 2, test material S9 (see Table 1) was used, which has a Mg content and a Bi content less than the specific ranges and contains almost no MgBi-based compounds. Since the amounts of Mg and Bi in test material S9 are small, the destruction of the oxide film during brazing heating is insufficient, and as shown in Table 2, the brazeability is inferior to test materials S1 to S8.

[0109] For the mini-core specimens 1 shown in experiment numbers A10 and A12 in Table 2, test materials S10 and S13 (see Table 1) were used, which have a Bi content less than the specific range and in which MgBi-based compounds are hardly formed. Since the amount of Bi in these test materials is small, the destruction of the oxide film during brazing heating is insufficient, and as shown in Table 2, the brazeability is inferior to that of test materials S1 to S8.

[0110] Test material S12 (see Table 1) having a Mg content higher than the specific range was used for mini-core test piece 1 shown in experiment number A11 in Table 2. Test material S12 is prone to growing an oxide film during brazing, and therefore has inferior brazability compared to test materials S1 to S8 as shown in Table 2.

[0111] Example 3 In this example, a mini-core specimen 1 is prepared by brazing in an inert gas atmosphere containing less moisture and oxygen than in Example 2, and the brazing property and buckling resistance are evaluated based on the brazing results of the mini-core specimen 1. Among the symbols used in this example, the same symbols as those used in the previous examples represent the same components as those in the previous examples unless otherwise specified.

[0112] [Preparation of mini-core specimen] The structure of the mini-core specimen 1 of this example is the same as that of the second example.

[0113] Specifically, any one of the test materials S15 to S17 in Example 1 or a plate material made of A3003 alloy and having a thickness of 0.20 mm is used as the plate 2. Also, any one of the test materials S18 to S20, S22, S24 in Example 1 or a plate material made of A3003 alloy and having a thickness of 0.070 mm is used as the corrugated fin 3.

[0114] In this example, the plate 2 is etched, and then combined with the corrugated fin 3 as shown in Table 3 to produce an assembly. The etching solution and etching conditions used for etching are the same as those in Example 2. The assembly is restrained using a stainless steel jig, and then placed in a brazing furnace for brazing. In this example, brazing is performed in a nitrogen atmosphere with an oxygen concentration of 1 ppm by volume and a dew point of -70°C. During brazing, the assembly is heated so that the time required for the temperature in the brazing furnace to reach 590°C from the time it reaches 580°C is 70 seconds.

[0115] By the above steps, it is possible to obtain the mini-core specimens 1 shown in the experiment numbers B1 to B3 in Table 3. The mini-core specimens 1 shown in the experiment numbers B4 to B8 in Table 3 are mini-core specimens 1 for comparison with the mini-core specimens 1 shown in the experiment numbers B1 to B3.

[0116] Table 3 shows the evaluation results of the brazeability and buckling resistance of the single-layer aluminum alloy material for brazing using the mini-core specimen 1 of this example. The evaluation method of the brazeability and buckling resistance was the same as in Example 2.

[0117] [Table 3]

[0118] Test materials S15 to S17 (see Table 1) having the specific chemical components were used for the mini-core test specimens 1 shown in Experiment Nos. B1 to B3 in Table 3. These test materials S15 to S17 exhibit excellent brazing properties even in an atmosphere with a relatively low moisture and oxygen content, and can increase the joining rate of the mini-core test specimens 1.

[0119] On the other hand, the mini-core specimen 1 shown in experiment number B4 in Table 2 uses the test material S18 (see Table 1) whose Si content is less than the specific range. The test material S18 has a smaller amount of molten liquid that can be supplied to the joined parts during brazing, and therefore has inferior brazability compared to the test materials S15 to S17 as shown in Table 3.

[0120] Test material S19 (see Table 1), which has a Si content higher than the specific range, was used for mini-core test piece 1 shown in experiment number B5 in Table 2. Test material S19 cannot maintain its strength because an excessive amount of molten liquid is formed during brazing, and as shown in Table 3, it is inferior in brazeability and buckling resistance to test materials SS15 to S17.

[0121] Test material S20 (see Table 1) having an Fe content less than the specific range was used for mini-core test piece 1 shown in experiment number B6 in Table 2. Test material S20 is prone to loss of strength at high temperatures, and is therefore inferior in brazeability and buckling resistance to test materials S15 to S17 as shown in Table 3.

[0122] Test material S22 (see Table 1) having a Mn content lower than the specific range was used for mini-core test piece 1 shown in experiment number B7 in Table 2. Test material S22 is prone to low strength, and is therefore inferior in brazeability and buckling resistance to test materials S15 to S17 as shown in Table 3.

[0123] For the mini-core specimen 1 shown in experiment number B8, test material S24 having a Cu content higher than the specific range is used as shown in Table 1. Test material S24 is prone to having low strength due to an excessively large amount of melting during brazing, and therefore is inferior in brazability and buckling resistance to test materials S15 to S17 as shown in Table 3. [Explanation of symbols]

[0124] 1 Mini core specimen 2 Plate 3. Corrugated fins 4. Fillet

Claims

1. The alloy has a chemical composition comprising: Si: 1.5% by mass or more and 3.5% by mass or less; Fe: 0.05% by mass or more and 2.00% by mass or less; Mn: 0.1% by mass or more and 2.0% by mass or less; Mg: 0.005% by mass or more and 0.500% by mass or less; Bi: 0.010% by mass or more and 0.500% by mass or less; and the balance being Al and unavoidable impurities; It has a metal structure in which MgBi-based compounds are dispersed in an Al matrix, A single-layer aluminum alloy material for brazing, wherein the area ratio of the MgBi-based compound in any cross section is 0.05% or more.

2. The brazing single layer aluminum alloy material according to claim 1, further comprising one or more elements selected from the group consisting of Zn: 6.0 mass% or less, In: 0.1 mass% or less, Sn: 0.1 mass% or less, Cu: 0.6 mass% or less, Zr: 0.3 mass% or less, and Ti: 0.3 mass% or less.

3. The brazing single layer aluminum alloy material according to claim 1 or 2, further comprising one or more elements selected from the group consisting of Sr: 0.1 mass% or less, Na: 0.1 mass% or less, and Sb: 0.3 mass% or less.

4. A method for producing an aluminum structure using the single-layer aluminum alloy material for brazing according to any one of claims 1 to 3, An assembly is produced, which includes the brazing single-layer aluminum alloy material and a mating material in contact with the brazing single-layer aluminum alloy material, and at least one of the brazing single-layer aluminum alloy material and the mating material is etched; In an inert gas atmosphere having a dew point of −50° C. or less and an oxygen concentration of 100 ppm by volume or less, the assembly is heated under heating conditions such that the temperature is within a range of 580 to 590° C. for 30 seconds or more, thereby melting a portion of the single-layer aluminum alloy material for brazing to form a molten liquid; The aluminum structure is manufactured by brazing the assembly with the molten liquid.

Citation Information

Patent Citations

  • JP1975021097A

  • Television receiver

    JP1978037326A

  • Aluminum alloy sheet for forming, and production method therefor

    JP2003089839A

  • Aluminum alloy sheet having excellent formability and its production method

    JP2007169740A

  • Aluminum alloy material for monolayer heating joint, excellent in deformation resistance

    JP2019094517A